Artificial intelligence safety and security - Yampolskiy, Roman V. (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
This book includes chapters from leading AI Safety researchers, addressing different aspects of the AI control problem as it relates to the development of safe and secure artificial intelligence. The book would be the first to address challenges of constructing safe and secure artificially intelligent systems. No similar book currently exists that concentrates on technical aspects of this research from the computer science point of view. Competing books are aimed at general/non-professional audiences from a philosophical point of view--
"A Chapman & Hall book."
Includes bibliographical references and index
CSE
Parama
Keywords: Automation -- Safety measures; Automation -- Security measures; Artificial intelligence -- Safety measures; Artificial intelligence -- Moral and ethical aspects; Computer science